2013
DOI: 10.5551/jat.17632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Reduction Therapy on Obstructive Sleep Apnea Syndrome and Arterial Stiffness in Patients with Obesity and Metabolic Syndrome

Abstract: Aim: Obesity and metabolic syndrome (MetS) and obstructive sleep apnea (OSA), which are often accompanied by obesity, are each independently associated with cardiovascular disease (CVD). However, the influence of OSA on arterial stiffness in obese patients remains unclear. We herein examined the relationships between the severity of OSA and CVD risk factors, including the severity of MetS and arterial stiffness, in obese patients. In addition, we evaluated the effects of weight reduction therapy on OSA and art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 32 publications
4
36
0
Order By: Relevance
“…We previously reported that 3-month weight reduction therapy significantly reduced several cardiovascular risk factors, such as oxidized LDL (an atherogenic lipoprotein), an atherogenic index, and obstructive sleep apnea syndrome [17,19,28]. It was also reported that within the general population, falls in IAFA within 1 year were associated with a significant decrease in the number of metabolic risk factors, irrespective of BMI [29].…”
Section: Discussionmentioning
confidence: 95%
“…We previously reported that 3-month weight reduction therapy significantly reduced several cardiovascular risk factors, such as oxidized LDL (an atherogenic lipoprotein), an atherogenic index, and obstructive sleep apnea syndrome [17,19,28]. It was also reported that within the general population, falls in IAFA within 1 year were associated with a significant decrease in the number of metabolic risk factors, irrespective of BMI [29].…”
Section: Discussionmentioning
confidence: 95%
“…The principles of CAVI measurement were previously described by Yamabe et al 11) . Classical cardiovascular risk factors, including body mass index (BMI), and the cluster of risk factors comprising metabolic syndrome (MetS), are positively associated with arterial stiffness [12][13][14] . However, there Wen Wen and Bin Peng contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both studies indicate that subjects with obesity and OSA have a higher risk of arterial stiffness. Iguchi et al 16) recently reported a significant correlation with severe NIH and increased arterial stiffness. The interaction test showed a trend for an overweight status to be a modifier of the association between OSA and increased arterial stiffness (p = 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Short-and long-term continuous positive airway pressure (CPAP) therapy was found to significantly reduce CAVI 15) . It has also been shown that short-term weight reduction therapy improves not only metabolic dysfunction, but also the severity of OSA and arterial stiffness, as measured by CAVI 16) . The measurement of CAVI has demonstrated good reproducibility and was not affected by the blood pressure during measurement 17,18) .…”
Section: Assessment Of Nihmentioning
confidence: 99%